2003
DOI: 10.1016/s1607-551x(09)70436-x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Social Support and Health Outcomes: A Meta‐analysis

Abstract: The purpose of this study was to examine the relationship between social support and health outcome variables, and the effect size of social support on health outcomes. Meta-analysis was used to synthesize the primary studies identified initially from a computer search of the literature in Taiwan. Through preliminary screening related to the inclusion criteria, 165 dissertations and theses and 43 journal articles were included in this study. Finally, 182 primary studies, including 145 dissertations and theses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 17 publications
7
96
1
4
Order By: Relevance
“…These authors proposed that enhancing emotional wellbeing should hold the same significance as other aspects of animal care, such as nutrition and veterinary care. In humans, social support (positive human interactions) facilitates coping during times of stress and decreases susceptibility to disease (Wang et al, 2003). Even looking at a photograph of a favourite person increases IgA concentration (Matsunaga et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These authors proposed that enhancing emotional wellbeing should hold the same significance as other aspects of animal care, such as nutrition and veterinary care. In humans, social support (positive human interactions) facilitates coping during times of stress and decreases susceptibility to disease (Wang et al, 2003). Even looking at a photograph of a favourite person increases IgA concentration (Matsunaga et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Social support helps people to cope with stressful events and can enhance medical and mental well-being. Several studies have demonstrated that social support is effective in alleviating the effects of acute and chronic physical and mental health problems [16][17][18][19]. The concept of social support distinguishes between four types of support: (1) emotional support, (2) instrumental support, (3) informational support, and (4) appraisal support [20].…”
mentioning
confidence: 99%
“…The direct effect of social support on health revealed that the higher the social support, the lower the health disturbance. This negative relationship finding corresponded to that of Wang et al (2003). In Wang's meta-analysis, she divided the health construct into four facets and examined the relationship between social support and various health facets.…”
Section: The Role Of Social Support In the Stresshealth Processmentioning
confidence: 76%
“…Stress and health are multidimensional constructs (Wang, Wu, & Liu, 2003;Wheaton, 1999). As for stress, this current study combined various kinds of stress types, such as caregivers' stress, stress of military service, disaster stress, work stress, practicum stress, illness stress, stress of students' life, and so on.…”
Section: Conceptualization and Classification Of Stress And Health Comentioning
confidence: 99%